The Balassa-Samuelson Hypothesis in Developed Countries and Emerging Market Economies: Different Outcomes Explained - José García Solanes; Fernando Torrejón-Flores (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
This paper studies the Balassa-Samuelson effects in two areas with strong differences in economic development, sixteen OECD countries and sixteen Latin American economies. The USA is taken as a benchmark. Applying recent panel cointegration and bootstrapping techniques that solve for cross-sectional dependence and small panel size problems, we find some evidence for not rejecting the whole hypothesis in the LA area. In the context of OECD group, the second stage of the BS hypothesis, which relates relative sector prices with the real exchange rate, does not hold, probably because national markets remain to some extent segmented, as reflected in departures from PPP in the tradable sectors.
Keywords: F31; C15; E31; 330; Balassa-Samuelson effect; panel cointegration; cross-sectional dependence; bootstrap; economic development; Balassa-Samuelson Effekt; Wechselkurssystem; Entwicklung; Bootstrap-Verfahren; Vergleich; Entwicklungsländer; Schwellenländer; Aufstrebende Märkte